Characterizing the metabolites and the microbial communities of the soy sauce mash affected by temperature and hydrostatic pressure. (September 2019) - Liang, Ru; Huang, Jun; Wu, Xueming; Xu, Yi; Fan, Jun; Wu, Chongde; Jin, Yao; Zhou, Rongqing
Abstract: The effect of hydrostatic pressure (HSP) and constant temperature fermentation (CTF) on the microbial community of soy sauce mash and metabolites (volatile and non-volatile) in raw soy sauce were investigated by multiphase methods. Soy sauce inoculated with yeasts (YG) or a mixture of yeasts and bacteria (MYG) were used in the present research. The results suggested that the effect of HSP resulted in decreasing of fungal community diversity, while CTF caused changes of the evenness of fungi species, which were also confirmed by alpha/beta diversity and clustering analysis. The volatile compounds analysis indicated that the total volatiles decreased by 47.53% in the raw soy sauce fortified by MYG under HSP, while that of organic acids and free amino acids were increased. The effect of CTF on volatile compounds depended on the fortified pattern. The community diversity and metabolite features between fortified and conventional soy sauce were also different. Graphical abstract: Unlabelled Image Highlights: Effect of HSP on microbial community and metabolites of soy sauce was first studied. Microbial community and metabolites were more sensitive to temperature than HSP. Higher RS and lower Esters levels were observed in MYGH. Fermentation conditions affect microbial interaction relationship. Volatile compounds closely related to domain microbes.